2021
DOI: 10.3390/clinpract11010020
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Pediatric Robot-Assisted Pyeloplasty in A Low-Volume Centre

Abstract: (1) Background: This study investigated the introduction of pediatric robot-assisted pyeloplasty in a low-volume centre with reference to open pyeloplasty with regards to operative times, length of stay (LOS) and outcomes and cost analysis. (2) Methods: Data from 10 consecutive robot-assisted pyeloplasties was compared retrospectively to an age and weight matched cohort of open pyeloplasties operated on during two previous years. Operative times were analyzed in conjunction with LOS, outcomes and cost-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In 2016, Bennett et al [67] found that charges for operative room time and supplies together with anesthesia time dominate the cost difference between RALP and open pyeloplasty, and that efforts to reduce these specific costs should be the focus of future cost-containment measures. A recent work published in 2021 [68] confirmed a similar cost burden of operating theater, instruments, material, and ward convalescence between open and RALP and justified the use of RALP in a low-volume center. The procedure required for double-J stent removal represented an additional cost.…”
Section: Cost Considerationsmentioning
confidence: 87%
“…In 2016, Bennett et al [67] found that charges for operative room time and supplies together with anesthesia time dominate the cost difference between RALP and open pyeloplasty, and that efforts to reduce these specific costs should be the focus of future cost-containment measures. A recent work published in 2021 [68] confirmed a similar cost burden of operating theater, instruments, material, and ward convalescence between open and RALP and justified the use of RALP in a low-volume center. The procedure required for double-J stent removal represented an additional cost.…”
Section: Cost Considerationsmentioning
confidence: 87%
“…While robot-assisted surgery presents many advantages over traditional laparoscopy through increased dexterity and improved and magnified optics, it has been criticized, especially from economic considerations [ 2 ]. Looking at hospital costs, irrespective of robotic acquisition costs, most aspects considered, robot-assisted pyeloplasty is feasible [ 3 ]. Pediatric RALP has also proven safe during the learning process [ 4 ], but the length of the learning process is open for debate with a range of numbers required for proficiency [ 5 ].…”
Section: Introductionmentioning
confidence: 99%